2021
DOI: 10.1007/s00604-021-04984-x
|View full text |Cite
|
Sign up to set email alerts
|

Excitation-emission fluorescence matrix acquired from glutathione capped CdSeS/ZnS quantum dots in combination with chemometric tools for pattern-based sensing of neurotransmitters

Abstract: The presented work concerns pattern-based sensing with quantum dots for the identification and quantification of neurotransmitters by means of excitation-emission fluorescence spectroscopy (2D fluorescence). In the framework of this study, glutathione capped CdSeS/ZnS nanocrystals were used as non-specific nanoreceptors capable of differentiated interaction with neurotransmitters. The pattern-based sensing with QDs was realized by using excitation-emission fluorescence spectroscopy to provide analyte-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Similarly, the RF-BLSTM model outperformed the BLSTM model by decreasing the value of RMSE by 70, 51, and 36% for the training, validation, and test set, respectively. Previous research indicates that the small values of MSE (and also RMSE) and the large value of R 2 are evidence that the model does not tend to overfit, and the model has excellent performance and accuracy. Also, additional statistical analyses were shown in Tables S3 and S4, which indicate the superiority of the RF-BLSTM model over the BLSTM model.…”
Section: Resultsmentioning
confidence: 89%
“…Similarly, the RF-BLSTM model outperformed the BLSTM model by decreasing the value of RMSE by 70, 51, and 36% for the training, validation, and test set, respectively. Previous research indicates that the small values of MSE (and also RMSE) and the large value of R 2 are evidence that the model does not tend to overfit, and the model has excellent performance and accuracy. Also, additional statistical analyses were shown in Tables S3 and S4, which indicate the superiority of the RF-BLSTM model over the BLSTM model.…”
Section: Resultsmentioning
confidence: 89%
“…Also, the CNN model surpassed DNN by a decrease of 47, 7, and 33% of RMSE in the train, validation, and test set, respectively. The previous publications revealed that the lower value of MSE and RMSE and the higher value of R 2 led to better models’ performance and accuracy. , What is more, small values of RMSE (also MSE) indicated that the obtained models are not susceptible to overfitting . Thus, there may be a slight tendency for overfitting in the test set of DNN, where the values of MSE and R 2 are 81.05 and 93.28%, respectively.…”
Section: Results and Discussionmentioning
confidence: 91%
“…62,63 What is more, small values of RMSE (also MSE) indicated that the obtained models are not susceptible to overfitting. 64 Thus, there may be a slight tendency for overfitting in the test set of DNN, where the values of MSE and R 2 are 81.05 and 93.28%, respectively. Altogether, these results indicate the superiority of CNN for qualitative and quantitative analysis of VB6Ds over DNN.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Głowacz et al 171 developed a strategy based on excitation–emission fluorescence spectroscopy using glutathione-capped CdSeS/ZnS quantum dots (QDs-GSH) for the detection of various neurotransmitters, including EP, NE, GABA, and more, because of the cross-affinity of the modified nanocrystals toward different chemical structures of neurotransmitters. The proposed assay allowed the quantification of catecholamine neurotransmitters (epinephrine, norepinephrine, and dopamine) at the micromolar concentration range.…”
Section: Sensors and Biosensors Based On Nanomaterials In The Detecti...mentioning
confidence: 99%